Measuring Surface Binding Thermodynamics and Kinetics by using Total Internal Reflection with Fluorescence Correlation Spectroscopy: Practical Considerations - Thompson, Nancy L. (2010)
The combination of total internal reflection illumination and fluorescence correlation spectroscopy (TIR-FCS) is an emerging method useful for, among a number of things, measuring the thermodynamic and kinetic parameters describing the reversible association of fluorescently labeled ligands in solution with immobilized, nonfluorescent surface binding sites. However, there are many parameters (both instrumental and intrinsic to the interaction of interest) that determine the nature of the acquired fluorescence fluctuation autocorrelation functions. In this work, we define criteria necessary for successful measurements, and then systematically explore the parameter space to define conditions that meet the criteria. The work is intended to serve as a guide for experimental design; in other words, to provide a methodology to identify experimental conditions that will yield reliable values of the thermodynamic and kinetic parameters for a given interaction.